Collagen regeneration template in the management of full-thickness wounds: a prospective multicentre study. (1st August 2019) - Alet, Jean-Maxime; Michot, Audrey; Desnouveaux, Emilie; Fleury, Marion; Téot, Luc; Fluieraru, Sergiu; Casoli, Vincent
Abstract : Objective: To evaluate the tolerance and healing rate of a collagen regeneration template in covering full-thickness wounds, including rate of adverse events. Method: In this prospective, multicentre study, patients with a full-thickness wound underwent two-stage surgery consisting of implantation of a collagen regeneration template followed by a split-thickness skin graft (STSG). Patients were followed-up for 12 months. Adverse events arising from either the implantation or STSG were evaluated. Results: Of the 33 patients included in the study, 29 completed the full follow-up period. During the study, 13 adverse events occurred at the treated wound site, as reported by 11 patients during follow-up. These included local infection (n=5), a diffuse infection (n=1) and non-infectious seroma under the silicon layer (n=1). The mean percentage of take of the collagen template at 21±7 days after implantation was 81.2% of the treated surface. The mean percentage of take of STSG at 28 days after grafting was 84.4% of grafted surface. STSG was successful in 28 patients, but was completely rejected at 12 months for one patient. Mean functional score at 12 months, as evaluated by the treating surgeons, was 76.8/100 and mean aesthetic score was 62.7/100. Conclusion: This study found use of a collagen regeneration template to be a safe procedure for the coverage of full thickness-wounds.